Rızaeddin Fahreddin’in derlediği “til yarışı” (metin-inceleme) - Bargan, Hüseyin (My University, 2008)
Bu çalışma, Şura dergisinin 1909’da düzenlemiş olduğu “Til Yarışı” (Kalem Müsabakası) adlı yarışmanın genel olarak metinlerini içermektedir. Daha sonra Rızaeddin Fahreddin’in, düzenleyip, 1910 yılında Orenburg’taki Vakit Matbaası’nda bastırmış olduğu Til Yarışı adlı 195 sayfalık kitabın incelemesidir. Bu çalışma altı bölümden oluşmaktadır: Giriş, İnceleme, Metin, Tercüme, Dizin ve Orijinal Metnin Fotokopisi. Giriş bölümünde, İdil-Ural bölgesinde Şura dergisi özelinde basın anlatılmıştır. İnceleme bölümünde, Şura’nı Til Yarışı, Rızaeddin Fahreddin ve Türk Dili, Türkçe’ye hizmet edenler ve Til Yarışı kitabının bölümleri ayrıntısıyla anlatılmış ve gramer çalışması yapılmıştır. Metin bölümünde, Arap harfli metin Tatarcalaştırılmadan Tatarca imlaya uygun olarak -ki Tataristan ve Başkurdistan’da sıkça yapılan bir hatadır- verilmiştir. Dördüncü bölümde; tercüme, beşinci bölümde; dizin, ve son bölümde de orijinal metnin fotokopisi verilmiştir.

This study is included and contained the Texts named “Til Yarısı” (Language Contest) organised by Sura Magazine in 1909 and is a research of Rızaeddin Fahreddin’s language contest book which had 195 pages held in Orenburg in 1910 and printed in Vakit Print House. This study has six sections: Introduction, Research, Text traslation, index and the Photocopy of the original Text. In introguction section; it is based on Sura Magazine for talking about the press in İdil-Ural region. Reseach section; grammar study was included the parts of the book named “Til Yarısı” (Language Contest) were mentioned and researched, and the servants of the Turkish Language and Rızaeddin Fahreddin’s literature. In text section; all the Arabic Letter texts are written and given to the readers in original statements not changed into Bashkurt and Tatar Language but spelling was kert the same as in the original text which is a mistake often made in Tataristan and Baskurdistan. In section four; there is the translation; in section five there is the index and in the last section: there is the photocopy of the original text.
Keywords: Türk Dili